Evaluation of antimutagenic activity and mechanisms of action of beta-glucan from barley, in CHO-k1 and HTC cell lines using the micronucleus test - Oliveira, Rodrigo Juliano; Ribeiro, Lucia Regina; da Silva, Ariane Fernanda; Matuo, Renata; Mantovani, Mario Sergio (Elsevier B.V., 2006)
Due to the need to identify new antimutagenic agents and to determine their mechanism of action, the present study examined the mechanism of action of the P-glucan with regard to antimutagenicity using the micronucleus assay in CHO-kl and HTC cell lines. The mutagenicity experiments were performed with three different concentrations of P-glucan (5, 10, and 20 mu g/mL), in wich only the highest dose showed mutagenic activity. In the antimutagenicity experiments, the same concentrations of P-glucan were combined with a mutagenic agent, methylmethane sulfonate, or 2-aminoanthracene, using four different treatment protocols: pre-treatment, simultaneous treatment (simple and with pre-incubation), and post-treatment. The results indicate that the CHO-kl cell line treated with MMS presented a chemopreventive activity for all the doses of P-glucan in the different treatment protocols, except for the lowest dose in post-treatment. When HTC cell line treated with MMS is analysed, a chemopreventive activity can be verified for the highest dose in both pre- and post-treatment. For the simple simultaneous treatment, the three doses demonstrated efficacy, while for the simultaneous treatment with pre-incubation only the intermediate concentration was effective. In HTC treated with 2AA both the lowest dose in the pre-treatment protocol and the post-treatment protocol did not show efficacy in preventing DNA damage. The evaluation of the different protocols and the damage decrease percentages observed suggest that P-glucan has both desmutagenic and bioantimutagenic activity. It is necessary, however, to note that efficacy and mechanism of action are subject to variation when compared the two cell lines, since in HTC, representing a drug-metabolizing system, this substance can show a diminished chemopreventive capacity. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-glucan; HTC cells; CHO-k1 cells; mechanism of action; antimutagenesis